Building proactive organizational resilience against the risk of major process safety incidents. Issue 1 (26th July 2022) - Qureshi, Muhammad Mushahid R.
Abstract: Major process safety incidents remain a key challenge to all industries involved in the handling, processing, manufacturing and transport of hazardous materials, including hydrocarbons. Over the past decade, there have been a number of incidents that have led to significant changes in the manner in which major industrial incidents are perceived and managed. Many companies adopt a traditional risk‐based approach when managing hazards. Larger organizations, such as oil and gas and petrochemical companies, can benefit from a proactive enterprise risk management (ERM) approach to build organizational resilience against potential threats to the business. While general risk management practices are focused on facility/asset level risks, the ERM approach offers a broader perspective when evaluating risks faced by businesses. The approach is flexible, dynamic, and cyclic in nature and provides a structured solution to the constantly evolving business risk environment. The results are intended to provide company executives with "a boardroom preview" of the risks faced and managed by the organization. This paper highlights the practical application of a six‐step ERM framework when assessing, analyzing, and recommending mitigation measures to bridge gaps related to managing major process safety risks. In addition, a structured methodology for the development and utilization of key risk indicators intended for continuous monitoring of process safety risks at a corporate level will be shared. Lessons learned from conducting this exercise will be discussed with practical advice on how to overcome commonly faced barriers.